2013
DOI: 10.1371/journal.pone.0080075
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Tasks Performed, Personality Traits, and Sleep Bruxism in Brazilian School Children - A Population-Based Cross-Sectional Study

Abstract: BackgroundTasks can be instruments of stress and may affect the health of children. Sleep bruxism is a multifactorial sleep-related movement disorder that affects children and adults. The aim of the present study was to analyze the association between children’s tasks, personality traits and sleep bruxism.Methods And FindingsA cross-sectional, population-based study of 652 randomly selected Brazilian schoolchildren (52% of whom were female), aged from 7 to 10 years was conducted in the city of Belo Horizonte, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0
15

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 37 publications
3
43
0
15
Order By: Relevance
“…4,6,15,22 No association with age was found, which is in agreement with findings described in previous studies. 1,3,6 Moreover, no association with mouth breathing was observed, although previous studies have found such an association. 16,23 Some variables reported to be associated with bruxism in the literature were not addressed in the present study, such as stress, level of responsibility, 3,15,17,19 excessive salivation, sleep walking, heredity, 13,15 the habit of chewing gum, biting on objects, 19 headache, 24 occlusal factors, impacted food scraps and extensive tooth decay.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…4,6,15,22 No association with age was found, which is in agreement with findings described in previous studies. 1,3,6 Moreover, no association with mouth breathing was observed, although previous studies have found such an association. 16,23 Some variables reported to be associated with bruxism in the literature were not addressed in the present study, such as stress, level of responsibility, 3,15,17,19 excessive salivation, sleep walking, heredity, 13,15 the habit of chewing gum, biting on objects, 19 headache, 24 occlusal factors, impacted food scraps and extensive tooth decay.…”
mentioning
confidence: 59%
“…2 In Brazil, the prevalence is 35.3% in the general pediatric population. 3 In children and adolescents with mental health problems (emotional symptoms, behavioral problems, peer problems, hyperactivity, etc. ), the rate ranges from 28.7% to 30.0%.…”
Section: Introductionmentioning
confidence: 99%
“…Although none of the questions was assumed as right, the FTQ showed greater coherence with factors already recognized as associated with childhood bruxism, considering behavioral and sleep characteristics 5,8,10,[12][13][14][15] . The AASM recommends the evaluation of the occurrence of audible teeth grinding during the night as a criterion for the definition of PSB 1 , however it does not indicate any validated questionnaire for this purpose.…”
Section: Discussionmentioning
confidence: 92%
“…The current scientific evidence about bruxism in children present various aspects that are still inconclusive, however, they already indicate that SB is more prevalent in younger children, with worse sleep quality and with anxious 8,9 or nervous behaviors 6,10,11 . Although none of the questions was assumed as right, the FTQ showed greater coherence with factors already recognized as associated with childhood bruxism, considering behavioral and sleep characteristics 5,8,10,[12][13][14][15] .…”
Section: Discussionmentioning
confidence: 99%
“…5,10 Sua etiologia psicológica está relacionada com a presença de ansiedade, hiperatividade e estresse ligados às tarefas do cotidiano, além de traços de personalidade. 11 Os fatores sistêmicos incluem alterações como a rinite, sinusite, asma e outras complicações respiratórias alérgicas. 12 O fator genético diz respeito à herança genética e sua contribuição substancial no fenótipo do bruxismo.…”
Section: 45unclassified